Керування навантаженням мережі на основі нечіткої логіки - Врублевський, А. Р.; Лісовий, І. П. (Видавництво Львівської політехніки, 2011)
In the thesis the questions of construction fuzzy logic routing systems are briefly described. The decision-making process based on fuzzy logic, which is the basis of the operation of fuzzy controllers is described. The problems of optimization of their basic parameters (ranges of variatin of linguistic variables, shape and mambership function parameters of linguistic quantities) are explained important for design of digital fuzzy controllers by minimizing the square-law perfomance criterion for the porpose of deriving optimum transient processes in fuzzy routing.
Keywords: fuzzy logic; linguistic variables; mambership function